Iowa Guidance Surveys. The Dropout Fiscal Year 1987. The Graduate--One Year after Fiscal Year 1986. - Iowa State Dept. of Education, Des Moines; Iowa State Dept. of Education, Des Moines ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
This document provides statistical data about dropouts and graduates of the Iowa public schools, presented in the form of tables and graphs. Much of the data is presented in enrollment categories based on size of the school population and merged areas. These tables and graphs are included: (1) fiscal 1987 secondary school dropout rates by enrollment categories and merged areas; (2) dropouts by gender in enrollment categories and merged areas; (3) grade distribution of dropouts by enrollment categories; (4) percentage of total enrollment versus percentage of total dropout population compared by enrollment categories; (5) percentage of total enrollment versus percentage of total dropout population compared by merged areas; (6) dropout information by county; (7) an 18-year composite for fiscal years 1970-1987 of dropouts by grade; (8) graduate follow-up totals for the state for 1986 showing type of post-high school education or type of employment or other occupation, also compared by enrollment categories and merged areas; and (9) an 18-year composite for fiscal years 1969-1986 for status of graduates. (ABL)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Dropout Rate; Dropout Research; Dropouts; Graduate Surveys; High School Students; High Schools; Outcomes of Education; Vocational Followup; Numerical/Quantitative Data